Using Leaflet-Based Interactive Learning Media to Increase Interest in Learning Social Sciences - Kori Sundari; Putri Damayanti Ardy Astuti; Arita Marini; Prayuningtyas Angger Wardhani (LPPM Undiksha, 2024)
Lack of student interest in learning impacts low student learning outcomes. Learning media is needed to support learning activities. This research aims to analyze the use of leaflet-based interactive learning media to increase interest in learning social sciences in fourth-grade elementary school. This type of research is experimental research. The research design used was Pretest-Posttest Non-Equivalent Control Group Design. The population of this study consisted of 50 fifth-grade elementary school students. The data collection method uses tests. The data collection instrument uses test questions. The data analysis technique uses inferential statistical analysis. The research results show significant value and no significant influence of the use of interactive learning media on the learning outcomes of the experimental and control groups. The findings show that handout-based interactive media in social studies teaching provides interactive handouts that attract less students' attention and engage them in learning. Attractive visual design and interactive features make learning less exciting and fun. The interactive nature of handouts allows students to interact with the content actively, enhancing their understanding of complex concepts. Additionally, the flexibility of interactive handouts does not allow for a learning experience that is personalized and tailored to each student's needs and preferences. These findings have significant implications for the design and implementation of educational materials in the future.